Pertanggung Jawaban Notaris Terhadap Penerbitan Covernote Ditinjau Dari Perspektif Undang-Undang Jabatan Notaris - Putra, Restu Adi; Rato, Dominikus; Dwi Anggono, Bayu; Cahyo Setiono, Gentur (LPPM Universitas Ekasakti Padang, 2024)
A covernote is a statement letter containing the notary's ability to carry out what the debtor wants. The notary has full responsibility for the contents contained in a cover note. Covernotes are not textually part of the authority of a Notary, this is interesting to study in more depth regarding the form of notary responsibility for the covernote that has been made. The research method used in this research is a normative juridical method. The conclusion obtained is that covernotes are not part of the authority of a notary as regulated in the Law on the Position of Notaries, but are a habit that grows and develops in society and is made into customary law. So that the notary's responsibility regarding the covernote that is made can be called for criminal, civil or moral sanctions imposed by the community.